Modificações em longo prazo na ictiofauna da planície de inundação do alto rio Paraná, Brasil. - Oporto, Lorena Torres (2008)
In this paper were investigated the modifications in fish fauna of the rivers of Upper Paraná River floodplain after the introduction of species due to the submerging of Sete Quedas Falls, still covering the period of construction of Porto Primavera dam. Samples were taken monthly from Oct/1986 to Sept/1988 and Mar/1992 to Feb/1994, bimonthly from Apr/1994 to Feb/1995, and quarterly from Feb/2000 to Nov/2002 and Mar/2004 to Dec / 2006 in Baía, Ivinheima and Paraná rivers, and the analysis covered only the most abundance species in four pre-determined periods. The tendency of dynamic population of the species was investigated by the effect size and their confidence intervals, and changes in the most abundant species were verified through rank-log abundance curve (Whitaker-plot). It could be conclude that in Baía and Ivinheima rivers introduced species are replacing native species. In Paraná river occurs replacement of species, however, this seems to be results by changes imposed by dams upstream.